Implementation of a Tranexamic Acid Protocol to Reduce Blood Loss During Cranial Vault Remodeling for Craniosynostosis. Issue 6 (September 2016) - Martin, David T.; Gries, Heike; Esmonde, Nick; Diggs, Brian; Koh, Jeffrey; Selden, Nathan R.; Schreiber, Martin; Kuang, Anna A.
Abstract : Objective: Pediatric cranial vault remodeling for repair of craniosynostosis is associated with significant blood loss and transfusion requirements. Beginning in 2011, the authors evaluated the impact tranexamic acid (TXA) on blood loss and blood product transfusion for children less than 15 months of age undergoing primary surgical repair of nonsyndromic single suture craniosynostosis. Methods: Following institutional review board approval, the authors performed a retrospective study of all children undergoing surgical correction of craniosynostosis at Oregon Health & Science University from 2005 to 2015. All available records were reviewed, and patient data were collected from the time of preoperative evaluation until discharge, comparing patient and clinical variables before and after the implementation of perioperative TXA. Results: Of a total of 259 patients with craniosynostosis, 187 had nonsyndromic single-suture involvement; 69 of these patients (36.9%) received TXA. A single surgical team (AAK and NRS) performed all operations. Median age at the time of surgery was 8.1 months (interquartile range [IQR] of 6.0–9.8 months). The TXA group had a significant reduction in estimated intraoperative blood loss (26 mL/kg versus 36 mL/kg, P <0.001), cell saver volume transfused 6 mL/kg versus 10 mL/kg, P <0.001), red cell transfusion volume (32 mL/kg versus 42 mL/kg, P <0.001), exposure to plasma transfusion (0% versus 24% P <0.001), exposure to cryoprecipitate transfusion (0% versus 16%, P <0.001), and exposure to platelet transfusion (0% versus 7.6% P = 0.03). Despite reduced red cell transfusion, the TXA-treated patients exhibited similar postoperative hematocrits (30.4 versus 30.3 P = 0.906) to those not treated with TXA. Use of TXA was associated with reduced length of stay (4 days IQR 3–4 versus 4 days IQR 4–5, P <0.001) and reduced postoperative output from surgically placed drains (181 mL versus 311 mL P <0.001). There was no difference in postoperative complications between groups and no deaths in either group. Conclusions: The introduction of TXA for nonsyndromic single-suture synostosis repair at our institution has significantly reduced blood loss and blood product and plasma transfusion during and following primary cranial vault remodeling for single suture craniosynostosis. Postoperative hematocrit was similar in the TXA-treated and untreated groups despite reduced red cell transfusion in the treated group. In addition, TXA use in this population has eliminated the need for plasma transfusion, and is associated with a shorter hospital stay. No difference in postoperative complications was observed. Our data provide support for further investigation of TXA treatment to improve clinical outcomes in children undergoing pediatric cranial vault remodeling.